Management of Genre Program in Improving Adolescent Reproductive Health in Bengkulu City - Yogopriyatno, Jatmiko; Sanusi, Disfin (KnE Social Sciences, 2025)
This study aims to examine how the management of the Genre program can improve adolescent reproductive health in Bengkulu City, specifically at the Bengkulu City P3AP2KB Office. A qualitative, descriptive method was used, with data collection through observation, interviews, and documentation. The analysis followed three stages: data reduction, data presentation, and conclusions. Key aspects analyzed include program needs assessment, preparation and empowerment of human resources, implementation of Genre Program activities and services, and supervision and evaluation. The findings indicate that the management of the Genre program has not been effectively implemented, primarily due to several challenges. These include the absence of dedicated funding for the program, limited financial resources, low participation in socialization efforts, insufficient capacity-building activities for program managers, infrequent evaluation meetings, inadequate supervision through reporting and field visits. To improve the management of the Genre program, the study recommends planning and submitting proposals for dedicated funding, establishing partnerships with financially capable organizations, and enhancing coordination with PLKB officers, community stakeholders, schools, and Genre partners to increase participation and strengthen program supervision.